2020
DOI: 10.48550/arxiv.2012.01553
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 Contact Tracing and Privacy: A Longitudinal Study of Public Opinion

Abstract: There is growing use of technology-enabled contact tracing, the process of identifying potentially infected COVID-19 patients by notifying all recent contacts of an infected person. Governments, technology companies, and research groups alike have been working towards releasing smartphone apps, using IoT devices, and distributing wearable technology to automatically track "close contacts" and identify prior contacts in the event an individual tests positive. However, there has been significant public discussio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…Thus, in this context, it may be interesting to explore the views of non-users in greater detail and what drivers, if any, might influence a future adoption decision. This line of inquiry may consider the role of the digital divide both in terms of access to technology and technology self-efficacy or perceived ability to effectively use these applications, different sources of contract tracing apps (Hargittai et al, 2020;Simko et al, 2020), specific security features (Das et al, 2015;de Montjoye et al, 2018), persuasive messaging (Matt, 2021), and other mechanisms that support multi-stakeholder assurance and accountability (Lynn et al, 2021).…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in this context, it may be interesting to explore the views of non-users in greater detail and what drivers, if any, might influence a future adoption decision. This line of inquiry may consider the role of the digital divide both in terms of access to technology and technology self-efficacy or perceived ability to effectively use these applications, different sources of contract tracing apps (Hargittai et al, 2020;Simko et al, 2020), specific security features (Das et al, 2015;de Montjoye et al, 2018), persuasive messaging (Matt, 2021), and other mechanisms that support multi-stakeholder assurance and accountability (Lynn et al, 2021).…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…In addition, we draw on social contract theory (SCT) to extend the perspective of benefits beyond the emphasis on utilitarian benefits (Sun et al, 2015) and consider the role of both perceived health benefits and reciprocal benefits in determining acceptance and use of contact tracing applications. In disease outbreaks characterized by both large-scale and rapid transmission, high mobile contact tracing uptake can have a significant impact on the effectiveness of disease control in a community (Simko et al, 2020). At an individual level, benefits include increased awareness of risk and Covid-19 hotspots, perceptions of altruism and "the greater good," and improved safety of loved ones and the community as a whole, among others (Redmiles, 2020;Williams et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Research has found that these data uses have varying levels of public approval, with participants voicing privacy concerns across studies (e.g., [142,123,66,141,74,109]). But, have these new and expanded uses of personal data in the COVID-19 context altered Americans' views on data privacy more broadly?…”
Section: Privacy and Covid-19mentioning
confidence: 99%
“…Related to the pandemic context in which our work takes place, Zhang et al [142] find modest to low levels of support for government surveillance measures to combat the spread of COVID-19 in the US, like encouraging use of contact tracing apps or implementing immunity pass systems. Additionally, Simko et al [123] find that while participants acknowledge that the benefits of data sharing with the government during the pandemic outweigh the risks, a majority of participants doubted that the government would delete their data or use it solely for COVID-19 related purposes. Our research investigates views on government uses of data that are not directly related to COVID-19 relief efforts to gain a holistic view of how data privacy attitudes may have changed during the pandemic.…”
Section: Data Privacy and The Governmentmentioning
confidence: 99%
“…Location-based contact tracing techniques and studies about potential digital surveillance systems are presented in several papers [43,50,66]. Beyond the technical aspects, some surveys evaluate implementation issues, user mental concern, and hardware impact which is rarely covered by others [6,47,51,68,71,72,74]. There are surveys listing additional privacy and resiliency vulnerabilities [29,56].…”
Section: Using Other Techniques For Contact Tracingmentioning
confidence: 99%